Imitation in cross-cultural leadership development - Silberman, Tim (Missiology, 2018)
Strategies for the development of Christian leaders in cross-cultural ministry tend to focus on communicating essential knowledge and skills, yet the need to facilitate growth in godly character is arguably of greater importance. Throughout his writings the Apostle Paul regularly presents himself as a model to be imitated by his readers. Careful consideration of his use of imitation reveals an invaluable approach to the development of core gospel values in emerging leaders today. In cross-cultural leadership development this will require contextualization of both the developmental relationship and the expression of these gospel values. The cultural dimensions of power distance and individualism/collectivism are specifically considered for their impact. It is suggested that the intentional use of imitation by living consistently with and teaching these core gospel values will greatly enhance cross-cultural leadership development.